An interpretation of four selected paintings from Amron Omar’s Pertarungan / Leyla Bajoul Kakahi - Leyla , Bajoul Kakahi (2017)
Amron Omar is one of the significant and talented Malay artist who has been a full-time artist for 30 years. Although Amron’s works had left impressionable suggestions as his paintings creates unique identity, characters, and forms in figurative painting, which makes clearly and understandable one of the significant part of Malay culture. The aim of this study was seeking to identify and deep understanding social-cultural impacts and a relationship between the artist background and his paintings. This qualitative study drew upon to the Barrett’s (1994) Art Interpretation Theory. In this regard, four selected artworks of Amron Omar during 1980-2000 have been interpreted by personal interpretation. Due to refine result of personal interpretation and prevent any researcher bias, the communal interpretation through questionnaire has been employed. These supportive data have collected from 20 Malay and 20 non-Malay art students. Regarding this exploration, it could be said; Amron Omar has exclusively focused on martial art as the main character to picture himself in his artworks which illustrate him as the warrior who defied himself. His artworks have been mirroring the endless self-challenge to get stronger, learn from his mistakes, develop his skills and never give up on his desires. Amron’s artworks consciously or unconsciously were affected by his background, hometown (Kedah), the way his family (especially his father) brought him up along beside the affection of his society, culture, schooling time, friends. Subsequently, the Silat as the symbol of patriotism which is carrying the history and culture of Malay nation has ingrained into his spirit since the childhood. However, during 1970-1990 the announcement of national culture and revival Islam had fascinated Malay artists to illustrate their Malay identity and their culture also the artist has illustrated the Silat and Sarong to show his loyalty to the Islamic identity, Malay culture. Since the 1990s, Malaysian art experienced various kinds of artistic forms, visions, subject and media, and the Malay art was criticized by postmodern artists. In conclusion, Amron as loyal to his Islamic-Malay character in his work has defined himself for new self-challenge with an aesthetic and critical perspective on his owns artworks to explore the beauty of Silat. Conceptually, the struggle in the paintings is not between bad/evil and good or approve a winner or loser. In fact, these paintings have depicted self-challenges to develop, being better and proceed the successful.